Roadmap on printable electronic materials for next-generation sensors - Pecunia, Vincenzo; Petti, Luisa; Andrews, Joseph B.; Ollearo, Riccardo; Gelinck, Gerwin H.; Nasrollahi, Bahareh; Jailani, Javith Mohammed; Li, Ning; Kim, Jong H.; Ng, Tse Nga; Feng, Hanru; Chen, Zhizhou; et al. (Nano Futures, 2024)
The dissemination of sensors is key to realizing a sustainable, ‘intelligent’ world, where everyday objects and environments are equipped with sensing capabilities to advance the sustainability and quality of our lives—e.g. via smart homes, smart cities, smart healthcare, smart logistics, Industry 4.0, and precision agriculture. The realization of the full potential of these applications critically depends on the availability of easy-to-make, low-cost sensor technologies. Sensors based on printable electronic materials offer the ideal platform: they can be fabricated through simple methods (e.g. printing and coating) and are compatible with high-throughput roll-to-roll processing. Moreover, printable electronic materials often allow the fabrication of sensors on flexible/stretchable/biodegradable substrates, thereby enabling the deployment of sensors in unconventional settings. Fulfilling the promise of printable electronic materials for sensing will require materials and device innovations to enhance their ability to transduce external stimuli—light, ionizing radiation, pressure, strain, force, temperature, gas, vapours, humidity, and other chemical and biological analytes. This Roadmap brings together the viewpoints of experts in various printable sensing materials—and devices thereof—to provide insights into the status and outlook of the field. Alongside recent materials and device innovations, the roadmap discusses the key outstanding challenges pertaining to each printable sensing technology. Finally, the Roadmap points to promising directions to overcome these challenges and thus enable ubiquitous sensing for a sustainable, ‘intelligent’ world.
Keywords: Electronics materials; Mechanical sensors; Printable biosensor; Printable electronic material; Printable electronics; Printable gas/vapor sensor; Printable mechanical sensor; Printable photodetector; Printable radiation sensor; Printable temperature sensor; Radiation sensors; Vapour sensors; printable biosensors; printable electronic materials; printable gas/vapour sensors; printable mechanical sensors; printable photodetectors; printable radiation sensors; printable temperature sensors